Gestures recognition as a new information input device for automatic system control - Lomakina, Olena (Видавництво Львівської політехніки, 2010)
This paper presents the up-to-date approaches to solve tasks of automatic systems control, which use hand motion analyzer as a new information input device.
Keywords: hand motion recognition; automatic systems; principal component analysis; independent components analysis